The Influence Of Storytelling Method On Listening Skills Of Group B Children Of Pertiwi Viii Kindergarten, Simpung Layung Village, Muara Uya District, Tabalong Regency - Rizki Noor; Rofia Noor Farisa (Universitas muhammadiyah Banjarmasin, 2023)
The background of this study is the influence of storytelling methods on listening skills of group B children of Pertiwi VIII Kindergarten, Simpung Layung Village, Muara Uya District, Tabalong Regency. The purpose of this study was to determine the influence of storytelling methods on listening skills of group B children of Pertiwi VIII Kindergarten, Simpung Layung Village, Muara Uya District, Tabalong Regency. The type of research used is quantitative research with a Pre-Experimental approach using One Group Pretest-Posttest design. This study used a sample of 10 group B children. The instruments used are observation sheets and check lists. Data collection techniques in this study used observation and documentation techniques while data analysis in this study used SPSS 22. Based on the results of the study, it was shown that there was an influence of the storytelling method on the listening skills of group B children of Pertiwi VIII Kindergarten, Simpung Layung Village, Muara Uya District, Tabalong Regency. This can be seen after treatment to children three times, children can listen attentively, interpret, and can understand meaning.In addition, it is evident from the results of the analysis of the Statistical Paired Sample Test test with a sig value (2-tailed) result of 0.036<0.05 which means that Ho's hypothesis is rejected and Ha is accepted. So it can be concluded that there is an influence of storytelling methods on the listening skills of group B children of Pertiwi VIII Kindergarten, Simpung Layung Village, Muara Uya District, Tabalong Regency.